Family Influences on the Performance of the Chinese Family Businesses : A Systematic Review - Ong, Saw Leng (2015)
This review aims to investigate the current state of knowledge of the Chinese family business discipline in the People's Republic of China (PRC) inclusive of the Mainland China, Hong Kong and Taiwan. The review also targets to study the influences of family ownership and control on the firms’ performance to determine if the family factors are of beneficial or detrimental effect to firm value. Throughout this review, a systematic approach is deployed to collect peer-reviewed articles from journals listed in the ProQuest and EBSCO databases with 31 articles identified in the end of the process. The outcome of the findings are mixed but in general, it suggests that the relationship between family ownership and firms’ performance in China are contingent to other family factors (family control and family management) as well as the contextual factors particularly the legal and regulatory institutions, market forces and cultural conventions.